2019
DOI: 10.1007/s11442-019-1591-4
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal distribution and transformation of cropland in geomorphologic regions of China during 1990–2015

Abstract: Landforms are an important factor determining the spatial pattern of cropland through allocation of surface water and heat. Therefore, it is of great importance to study the change in cropland distribution from the perspective of geomorphologic divisions. Based on China's multi-year land cover data (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 27 publications
2
32
0
Order By: Relevance
“…was used to calculate and analyze the LULC dynamic degrees in the study area from 1990 to 2016 [48]. The formula is as follows:…”
Section: Classification and Accuracy Assessment Methodsmentioning
confidence: 99%
“…was used to calculate and analyze the LULC dynamic degrees in the study area from 1990 to 2016 [48]. The formula is as follows:…”
Section: Classification and Accuracy Assessment Methodsmentioning
confidence: 99%
“…Spatial distribution characteristics of cultivated land in mountainous areas are directly related to topographic factors. Topography restricts the form and effectiveness of cultivated land use through the distribution of surface water and heat, which plays a vital role in determining cultivated land quality (Gao et al, 2019). Accordingly, the relief amplitude model is used to analyse the spatial distribution characteristics of cultivated land evolution in Southwest China.…”
Section: Topographic Relief Amplitude Extractionmentioning
confidence: 99%
“…Cultivated land is one of the most sensitive types of land‐use change (Gao et al, 2019), covering about 12.6% of global surface area (Han & Song, 2019). It plays a vital role in regulating climate change and ensuring food security and sustainable human development (Bren d'Amour et al, Fprogramme 2017; Rudel et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Landforms affect the allocation of surface water, heat, soil, and organisms to a significant extent, and thus may have great influence on the type of land use and the structure of farmland. Cheng et al (2018b) and Gao et al (2019) analyzed farmland conversion during 1990-2015 in the first-order geomor-regions. Studies indicated that the loss of farmland occurred mostly in Regions II and V as a result of growing industrialization and urbanization, whereas the increase of farmland occurred mainly in Regions I and IV because of reclamation of grassland and wasteland.…”
Section: Farmland Conversionmentioning
confidence: 99%